Pelaksanaan Program Muatan Lokal Keterampilan PKK di Sekolah Dasar Yogyakarta - Harti Kartini (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2006)
The study aims to evaluate the implementation of the local content subject, that is, Family Welfare Education, in two elementary school in Yogyakarta, focusing on the selection aspect, the program implementation, teacher's understanding, and factors affecting the program implementation. Utilizing observation, interviews, and documentation, the study reveals that the local content program was determinated by the school principals without considering teachers' view, student' interest, local needs, or parent' expectations. The Family Welfare Education was misunderstood as a subject equipping students with knowledge of handicrafts and household affairs.